Respuesta:
1. [tex]2x^2-2x+2-\frac{3}{2x+1}[/tex]
2. [tex]2x-5+\frac{-26x+5}{3x^2-5x+2}[/tex]
Explicación paso a paso:
1. Procedimiento
[tex]\frac{\left(4x^3-2x^2+2x-1\right)}{\left(2x+1\right)}\\\\=2x^2+\frac{-4x^2+2x-1}{2x+1}\\\\=2x^2-2x+\frac{4x-1}{2x+1}\\\\=2x^2-2x+2+\frac{-3}{2x+1}\\\\=2x^2-2x+2-\frac{3}{2x+1}[/tex]
2. Procedimiento:
[tex]\frac{\left(6x^3-25x^2+3x-5\right)}{\left(3x^2-5x+2\right)}\\\\\frac{6x^3-25x^2+3x-5}{3x^2-5x+2}=2x+\frac{-15x^2-x-5}{3x^2-5x+2}\\\\=2x-5+\frac{-26x+5}{3x^2-5x+2}[/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
1. [tex]2x^2-2x+2-\frac{3}{2x+1}[/tex]
2. [tex]2x-5+\frac{-26x+5}{3x^2-5x+2}[/tex]
Explicación paso a paso:
1. Procedimiento
[tex]\frac{\left(4x^3-2x^2+2x-1\right)}{\left(2x+1\right)}\\\\=2x^2+\frac{-4x^2+2x-1}{2x+1}\\\\=2x^2-2x+\frac{4x-1}{2x+1}\\\\=2x^2-2x+2+\frac{-3}{2x+1}\\\\=2x^2-2x+2-\frac{3}{2x+1}[/tex]
2. Procedimiento:
[tex]\frac{\left(6x^3-25x^2+3x-5\right)}{\left(3x^2-5x+2\right)}\\\\\frac{6x^3-25x^2+3x-5}{3x^2-5x+2}=2x+\frac{-15x^2-x-5}{3x^2-5x+2}\\\\=2x-5+\frac{-26x+5}{3x^2-5x+2}[/tex]